Ultrasonography in neuralgic amyotrophy: Sensitivity, spectrum of findings, and clinical correlations. Issue 6 (15th June 2017) - ArÁnyi, Zsuzsanna; Csillik, Anita; DéVay, Katalin; Rosero, Maja; Barsi, PéTer; BÖhm, Josef; Schelle, Thomas
ABSTRACT: Introduction: The aim of this study was to assess the value of ultrasonography in neuralgic amyotrophy. Methods: Fifty‐three patients with 70 affected nerves were examined with high‐resolution ultrasound. Results: The most commonly affected nerve was the anterior interosseous (23%). Ultrasonographic abnormalities in the affected nerves, rather than in the brachial plexus, were observed, with an overall sensitivity of 74%. Findings included the swelling of the nerve/fascicle with or without incomplete/complete constriction and rotational phenomena (nerve torsion and fascicular entwinement). A significant difference was found among the categories of ultrasonographic findings with respect to clinical outcome ( P  = 0.01). In nerves with complete constriction and rotational phenomena, reinnervation was absent or negligible, indicating surgery was warranted. Discussion: Ultrasonography may be used as a diagnostic aid in neuralgic amyotrophy, which was hitherto a clinical and electrophysiological diagnosis, and may also help in identifying potential surgical candidates. Muscle Nerve 56 : 1054–1062, 2017